Mapping of Areas Suitable for Black Pepper (Piper nigrum L.) Cultivation in the Municipality of Baião-PA using Geoprocessing Techniques (REMUNOM, 2026)
Black pepper is one of the most important crops for the municipality of Baião, PA, generating employment and income for the local community. For this reason, understanding the factors that interfere with the production system is fundamental for the expansion of the crop. One of the alternatives to do this in a cheap and practical way is through the use of geotechnologies combined with Geographic Information Systems. The methodology adopted consisted of applying multi-criteria analysis, using the Analytic Hierarchy Process (AHP) technique. Through the results of this study, it was possible to identify areas with potential for the expansion of black pepper, considering the factors that affect its development. The study identified that the municipality has a high potential for expansion of the crop, with an area exceeding 66% of the total area of the municipality that can be used for black pepper cultivation. In addition to this quantification, it was possible to spatially identify these areas, identifying in which regions of the municipality these areas with high potential are located. Based on the results of this research, it will be possible to assist technicians and producers in making more assertive decisions for the implementation of this crop, which is of great importance to the municipality